Role of decreased androgens in the ovarian response to stimulation in older women - Meldrum, David R.; Chang, R. Jeffrey; Giudice, Linda C.; Balasch, Juan; Barbieri, Robert L. (Fertility and sterility, 2013)
Ovarian testosterone increases the response of antral follicles to stimulation, declines with age, and has effects mediated or potentiated by insulin-like growth hormone I (IGF-I). Increased circulating insulin and IGF-I, exogenous testosterone, and increased local ovarian testosterone concentrations due to aromatase inhibition or exogenous luteinizing hormone/human chorionic gonadotropin are all associated with an increased ovarian response to gonadotropins. These factors should be further investigated alone or in combination for enhancing oocyte yield with fertility treatments, particularly in older reproductive-age women.